Understanding Dynamics of School Discipline: : Examining Classroom Practices and Teachers’ Perspectives in a Primary School - Joshi, Isha (Voices of Teachers and Teacher Educators, 2024)
The research paper aims to shed light on the dynamics of school discipline practices within the context of a primary school in Delhi, exploring how the disciplinary ideal unfolds, assimilates, and becomes deeply ingrained in teachers’ beliefs and classroom practices. This qualitative study employed participant observation, informal interactions and interviews to explore differing perspectives, experiences, and contexts within which disciplinary practices are applied. The research addresses key questions, including the types of disciplinary methods commonly employed in primary schools, teachers’ perceptions of the effectiveness of these methods, and the factors influencing their disciplinary decisions. Participant observations address the disciplinary aspects of the activities and social hierarchies between students, teachers, and administrators, which form the basis of normative power. Interview results indicate that teachers view discipline as the ‘soul’ of any formal educational institution, and consider it to be a vital part of the school experience. The categories of order, rules, obedience, respect and service emerge as having the utmost priority among teachers’ perceptions of discipline.